Links Between Human Resource Management Practices, Work Motivation, and Work Commitment in Indonesia Banking - Zakyya Tunnufus; Juliansyah Noor (APMBA (Asia Pacific Management and Business Application), 2022)
This article proposes examining human resource management practices (HRMPs) and work motivation in influencing work commitment in the Indonesian banking industry. This research employs quantitative survey research. The survey data contains 277 employees from 11 Indonesian private commercial banks. To analyze the data, this study uses the multiple regression method. This study finds that HRMPs and work motivation positively predict work commitment. Results also identify work motivation as a positive predictor of work commitment. Therefore, HRMPs and work motivation make positive contributions to influencing work commitment. Research on links between HRMPs, WM, and WC is important but has not been studied. This article is hoped to be a novelty. It is expected to address an important gap in the human resource management literature. HRMPs, work motivation, and work commitment in the Indonesian banking industry can contribute to human resources management literature. Indonesia's banking industry is booming. As a result, there is a need for efficient and experienced human resource recruitment. This research will contribute to Indonesia's banking industry development.